The Asian liquidity crisis - Roberto Chang; Andres Velasco (Federal Reserve Bank of Atlanta, 1998)
A country's financial system is internationally illiquid if its potential short-term obligations in foreign currency exceed the amount of foreign currency it can have access to in short notice. This condition may be necessary and sufficient for financial crises and/or exchange rate collapses (Chang and Velasco 1998a, b). In this paper we argue that the 1997-98 crises in Asia were in fact a consequence of international illiquidity. This follows from an analysis of empirical indicators of illiquidity as well as other macroeconomic statistics. We trace the emergence of illiquidity to financial liberalization, the shortening of the foreign debt structure, and the currency denomination of assets versus liabilities. We explain how financial crises became exchange rate collapses due to a government policy of both fixing exchange rates and acting as lender of last resort. Finally, we outline the policy implications of our view for preventing crises and for dealing with them.
Keywords: 330; Banks and banking; Central; International finance; Liquidity (Economics); Monetary policy; Money supply